MGBK MAGIC MOODLE: Management Model to Enhance the Professionalism of Guidance and Counseling Teachers - Yari Dwikurnaningsih; Purwanti; Marinu Waruwu (Universitas Pendidikan Ganesha, 2024)
The implementation of comprehensive guidance and counseling in schools still needs improvement. Various factors, such as inadequate resources, can cause this shortage. This research aims to develop the MGBK MAGIC MOODLE management model to increase the professionalism of guidance and counseling teachers. This research uses a research and development methodology with a mixed methods approach. This validation process involves input from two expert validators. A small-scale trial involving 10 guidance and counseling teachers and a large-scale trial involving thirty guidance and counseling teachers. Data collection methods include interviews, questionnaires, and document analysis. The data collection instrument uses a questionnaire sheet. The data analysis techniques used are qualitative descriptive analysis and quantitative descriptive analysis. The research results show that ICT and management experts' validation results are very good. At the limited trial stage, the results showed an average score of 49.79% in the good category and 50.21% in the very good category. In the main field trial, the average score was 54.7% in the very good category, 44.6% in the good category, and 0.7% in the not good category. The results of the main field trial showed that the product effectiveness test provided very positive results. It was concluded that the MGBK MAGIC MOODLE management model successfully provided a practical impact in supporting MGBK management tasks. The MGBK MAGIC MOODLE management model has implications for enhancing the professionalism of counseling teachers through effective technology integration, thereby optimizing the implementation of comprehensive guidance and counseling in schools.